Análise da ação antimicrobiana e da substantividade de diferentes formulações de clorexidina comumente utilizadas durante o tratamento endodôntico - Souza, Matheus Albino (2013)
The purpose of this thesis was to evaluate, in vitro, antimicrobial activity and substantivity of chlorhexidine formulations which are used during root canal therapy. Eighty five bovine teeth and forty five human teeth were extracted for antimicrobial and substantivity experiments respectively. The eighty five bovine teeth were inoculated with Enterococcus faecalis in order to provide biofilm formation. The teeth were divided into ten groups according to disinfectant penetration, intracanal dressing and medication placement site. Microbiological test (UFCs counting) and scanning electronic microscopy (SEM) were performed to evaluate and illustrate the efficacy of proposed treatments respectively. The forty five human teeth were divided into three groups according to chemical auxiliary substance used during root canal therapy. The root canals were prepared up to #45 file. Longitudinal grooves were made in the root surface, providing two halves of each root and resulting in thirty samples per group. The samples of each group were randomly divided into three subgroups and substantivity was evaluated after 24 hours, 30 days and 90 days of incubation. The amount of CHX (in μM) was measured through reverse-phase high-performance liquid chromatography. Statistical analysis was performed by analysis of variance and the Tukey test for post hoc comparisons (α = 0.05) in both experiments. According to limitation of experiments from this thesis, it was possible to conclude that chlorhexidine formulations, liquid and gel, can be considered effectives as intracanal dressing against Enterococcus faecalis, when associated to previous disinfectant penetration with 2% sodium hypochlorite. Furthermore, it was possible to conclude that chlorhexidine formulations, liquid and gel, remained into the root canal up to 90 days after chemo-mechanical preparation.